Human cytomegalovirus UL44 concentrates at the periphery of replication compartments, the site of viral DNA synthesis - Strang, Blair L.; Boulant, Steeve (Journal of virology, 2012)
The formation of replication compartments, the subnuclear structures in which the viral DNA genome is replicated, is a hallmark of herpesvirus infections. The localization of proteins and viral DNA within human cytomegalovirus replication compartments is not well characterized. Immunofluorescence analysis demonstrated the accumulation of the viral DNA polymerase subunit UL44 at the periphery of replication compartments and the presence of different populations of UL44 in infected cells. In contrast, the viral single-stranded-DNA binding protein UL57 was distributed throughout replication compartments. Using “click chemistry” to detect 5-ethynyl-2′-deoxyuridine (EdU) incorporation into replicating viral DNA and pulse-chase protocols, we found that viral DNA synthesis occurs at the periphery of replication compartments and that replicated viral DNA subsequently localizes to the interior of replication compartments. The interiors of replication compartments also contain regions in which UL44 and EdU-labeled DNA are absent. The treatment of cells with a viral DNA polymerase inhibitor reversibly caused the dispersal of both UL44 and EdU-labeled viral DNA from replication compartments, indicating that ongoing viral DNA synthesis is necessary to maintain the organization of replication compartments. Our results reveal a previously unappreciated complexity of the organization of human cytomegalovirus replication compartments.
Published ahead of print 7 December 2011
Gesehen am 07.11.2018